Perspectives on the Theory of Defects - Spitaler, Jürgen; Estreicher, Stefan K. (Frontiers in Materials, 2018)
Our understanding of defects in materials science has changed tremendously over the last century. While one hundred years ago they were often ignored by scientists, nowadays they are in the spotlight of scientific interest and whole branches of technology have emerged from their skillful handling. The first part of this article gives a historical overview and discusses why defects are so important for modern material science. In the second part, we review the treatment of defects in semiconductors. We start by explaining the assumptions and approximations involved in ab-initio calculations and then discuss the treatment of defects in materials. In the third part, we focus on defects in metals. We discuss the theoretical treatment of vacancies in metals starting from experimental findings. The impact of improved theoretical techniques on the predictive power is discussed. This is illustrated with the role of vacancies in intermetallic compounds and random alloys. The last section deals with dislocations.